Preference toward investment-linked takaful plan: mediating role of attitude - Parveen, Tamiza; Razali, Siti Salwani; Che Mohd Salleh, Marhanum (Research Publishing Academy (RPA), 2019)
Investment-linked products (ILPs) are the latest innovations from the Islamic finance industry that offers investors the opportunity to get protection and investment through their family takaful plan. In this paper, we focus on exploring the preference toward investment-linked Takaful plan. Based on the propositions of the theory of interpersonal behaviour and the theory of Islamic consumer behaviour, we develop a conceptual model to investigate factors that could explain the preference toward investment-linked products (ILP). We have used a structured literature review to conduct a critical review of the literature. Attitude is positioned as mediation in the developed conceptual model. The conceptual model proposed in this study is the first of its kind and contributes to the existing literature of behavioural finance.